Tư tưởng Hồ Chí Minh về con người và về chính sách xã hội đối với con người - Lê, Sỹ Thắng (2011)
Tác giả: Lê Sỹ Thắng, PGS, PTS; Hoàng Tùng; Nguyễn Trọng Chuẩn, PGS, PTS; Bùi Đình Thanh, PGS -- Từ khóa: Tư tưởng Hồ Chí Minh; Con người; Chính sách xã hội; Hồ Chí Minh